2022
DOI: 10.1530/raf-22-0067
|View full text |Cite
|
Sign up to set email alerts
|

Habitual physical activity levels in women attending the one-stop infertility clinic: a prospective cross-sectional observational study

Abstract: Optimisation of lifestyle factors such as smoking and alcohol are encouraged to improve fecundability rates in the fertility setting. Currently, routine fertility consultations do not involve counselling or imparting advice regarding habitual physical activity (PA) and/or structured exercise, despite data showing that vigorous PA can be associated with delayed time to pregnancy. Therefore, this study aimed to determine habitual PA in a sample of women attending the one stop infertility (OSI) clinic. 250 women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…It is well-established that the assessment of cardiometabolic risk in the preconception phase is advantageous as individuals with poor cardiometabolic health are more susceptible to hypertensive disorders such as pre-existing hypertension, gestational hypertension, preeclampsia and gestational diabetes during pregnancy ( 50 ). Further, evidence from pregnancy literature provides a strong rationale for physical activity participation to improve biophysical markers (e.g., HDL-cholesterol, blood pressure, blood glucose and triglycerides), cardiorespiratory fitness and pregnancy outcomes ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-established that the assessment of cardiometabolic risk in the preconception phase is advantageous as individuals with poor cardiometabolic health are more susceptible to hypertensive disorders such as pre-existing hypertension, gestational hypertension, preeclampsia and gestational diabetes during pregnancy ( 50 ). Further, evidence from pregnancy literature provides a strong rationale for physical activity participation to improve biophysical markers (e.g., HDL-cholesterol, blood pressure, blood glucose and triglycerides), cardiorespiratory fitness and pregnancy outcomes ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Findings from epidemiological studies suggest associations between exercise (e.g., adherence to recommended guidelines of at least 150-min per week of moderate-intensity aerobic physical activity) and fertility outcomes, such as increased live birth or cumulative live birth [i.e., the preferred primary outcome for infertility research trials based on the “Improving the Reporting of Clinical Trials of Infertility Treatments” (IMPRINT) guidelines] ( 17 , 23 , 53 ). Yet, a recent study found that more than half of the women visiting a fertility clinic did not regularly participate in moderate or high-intensity exercise ( 50 ). There is an urgent need for the reproductive field to move beyond weight-centric approaches that recognize the limitations of a BMI measure and the potential benefits of exercise prescription for fertility care.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the findings of a previous study, which demonstrated that high intensity and frequency of physical activity have a negative impact on female reproductive health [ 14 ]. However, other studies have discovered no significant link between physical activity and female infertility, [ 16 19 ] or have indicated that physical activity may actually act as a protective factor against infertility [ 15 ]. We believe that the divergence in research findings is likely due to the studies not considering the independent effects that different types of physical activity may have on the human body, as well as the lack of adjustment for certain confounding factors or the selection of appropriate inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, another study proposed that insufficient physical activity could also have detrimental effects on fertility [ 15 ]. However, the majority of studies have reported no significant correlation between physical activity and infertility [ 16 19 ]. These conflicting findings not only generate controversy but also underscore the need for independent estimate of the relationship between different types of physical activity and infertility.…”
Section: Introductionmentioning
confidence: 99%